Method optimisation and validation study on use of laser doppler flowmetery to assess microvascular endothelial function - Rasool, Aida Hanum Ghulam; Rahman, Abdul Rashid Abdul (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
Introduction: Human postocclusive forearm skin reactive hyperemia is not only a potential means of identifying early signs of cardiovascular diseases, it can also be used in the assessment of local microvascular response to topically applied compounds on skin. The method is not fully characterized. In this study, we investigated the influence of occlusion time on postocclusive forearm skin reactive hyperemia using laser Doppler fluximetly (LDF). Methods: Twenty healthy male volunteers were studied on three separate days (at least 24 lti h apart) via a randomized design. Volunteers were studied in a supine position while fasted. Laser Doppler probes were placed on the volar surface of the antebrachium. In preliminary studies, 3 min of upper arm blood flow occlusion at suprasystolic pressure was found to be the upper limit of tolerability. Subsequently, volunteers were randomized to receive 1, 2, or 3 min occlusion on 3 different days. Skin blood flux 1~ was measured before, during, and after occlusion using LDF. The primary outcome calculated was maximal change in ski11 blood flux before and after occlusion, expressed in arbitrary units (AU). Results: Skin blood flux changes (mean ± S.E.M.) after 1, 2, and 3 min occlusion period were 15.39 ± 1.27 AU, 24.84 ± 1.62 AU, and 32.14 ± 1.73 AU, respectively. Using repeated-measures analysis of variance (ANOVA), significant difference (P<.OS) in skin blood flux changes were revealed between these three occlusion durations, where 3 min occlusion produced significantly greater in skin blood flux occlusion change compared to I and 2 min occlusion. Conclusion: Three minutes of occlusion produces the greater postocclusive reactive hyperemia. It is recommended that studies using postocclusive forearm skin reactive hyperemia should occlude the forearm for at least 3 min.